Review of Scirtidae (Coleoptera: Scirtoidea) described by Johan Christian Fabricius (1745–1808) - Ruta, Rafał (Zootaxa, 2013)
Scirtidae described by J. Ch. Fabricius are listed. Poorly known South American and Indian species are redescribed, illus-trated and figured. Cyphon depressus Fabricius is transferred to Ora Clark, and Cistela livida Fabricius is transferred to Pseudomicrocara Armstrong. Ora complanata (Guérin-Méneville) is probably a junior synonym of Ora depressa (Fabr-icius). Data on Scirtidae collections studied by Fabricius are summarized.